Higher Education and Students from Refugee Backgrounds: A Meta-Scoping Study. (16th January 2019) - Ramsay, Georgina; Baker, Sally
Abstract: Empirical interest in exploring the settlement experiences of people from refugee backgrounds has long been an area of research interest and advocacy. In particular, there has been significant growth in research that focuses on students from refugee backgrounds as they navigate the education systems of these settlement contexts, with a particular focus on refugee children and youth in schooling contexts. Less is known about the experiences of students from refugee backgrounds in higher education. This article speaks to this gap in our collective knowledge, offering a meta-scoping study of 46 papers on students from refugee backgrounds in international higher education contexts. A key contribution of this article is its holistic view of higher education – as it explores higher education in both refugee camp situations in countries of first asylum and countries of settlement – as well as its attention to the theoretical and methodological frames that have been used to make sense of the experiences of these students. From our reading of the field, we offer an analysis of the gaps in the literature, and propose a research agenda for further advancing both our collective understandings and the possibilities for institutional transformation and advocacy with these students.